2007
DOI: 10.1200/jco.2006.10.2517
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Stage III Epithelial Ovarian Cancer: A Gynecologic Oncology Group Study

Abstract: Age, PS, tumor histology, and residual tumor volume were independent predictors of prognosis in patients with stage III EOC. These data can be used to identify patients with poor prognosis and to design future tailored randomized clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

27
535
7
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 788 publications
(581 citation statements)
references
References 38 publications
27
535
7
12
Order By: Relevance
“…1,2 Some studies have showed that the endometrioid histology is associated with a better outcome than the serous histology. [2][3][4] In contrast, other studies have shown that when patients with endometrioid and serous tumors of the ovary are matched for age, tumor grade, disease stage, and level of cytoreduction, there is no difference in either the rate of 5-year survival or the mean/median length of survival. 5 The most commonly used grading systems have been those of the International Federation of Gynecology and Obstetrics (FIGO), the World Health Organization (WHO), and the Gynecologic Oncology Group (GOG).…”
mentioning
confidence: 93%
“…1,2 Some studies have showed that the endometrioid histology is associated with a better outcome than the serous histology. [2][3][4] In contrast, other studies have shown that when patients with endometrioid and serous tumors of the ovary are matched for age, tumor grade, disease stage, and level of cytoreduction, there is no difference in either the rate of 5-year survival or the mean/median length of survival. 5 The most commonly used grading systems have been those of the International Federation of Gynecology and Obstetrics (FIGO), the World Health Organization (WHO), and the Gynecologic Oncology Group (GOG).…”
mentioning
confidence: 93%
“…Patients with stage I MuOC have a 5‐year survival rate of 91%, whereas patients with recurrent disease or those diagnosed in an advanced stage usually die of the disease. The prognosis is significantly worse for patients with advanced‐stage MuOC than for patients with other histological subtypes of advanced‐stage ovarian cancer 5. The reason for this appears to be related to the frequency of platinum resistance in patients with MuOC 6.…”
mentioning
confidence: 99%
“…1,2 Factors that are believed to impact survival include patient age, performance status, preoperative CA125, volume of ascites, stage, grade, extent of cytoreductive surgery, chemotherapeutic agents, route of delivery, duration of treatment, histological subtype, host immune response, and specific genetic alterations, including BRCA mutations. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] There remains, however, limited ability to accurately prognosticate in patients with advanced stage high-grade serous carcinoma based on features of the primary tumor at the time of diagnosis.…”
mentioning
confidence: 99%